2000
DOI: 10.2307/1593088
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibody to Turkey Coronavirus by Antibody-Capture Enzyme-Linked Immunosorbent Assay Utilizing Infectious Bronchitis Virus Antigen

Abstract: An antibody-capture enzyme-linked immunosorbent assay (ELISA) for detection of antibody to turkey coronavirus (TCV) utilizing infectious bronchitis virus (IBV) antigen was developed. Anti-TCV hyperimmune turkey serum and normal turkey serum were used as positive or negative control serum for optimization of the ELISA system. Goat anti-turkey immunoglobulin G (light plus heavy chains) conjugated with horseradish peroxidase was used as detector antibody. The performance of the ELISA system was evaluated with 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 5 publications
4
37
2
Order By: Relevance
“…In addition, basal lamina was infiltrated with mononuclear cells, presented submucosa oedema compatible with viral enteritis (results not shown). These findings have been described for PEMS, however they are common to other enteric pathogens [6][7][8] . Regarding to the intestines analyzed here, they were flaccid, thin-walled, and filled with loose contents, and the disease was acute, with symptoms appearing and lasting for about 3 weeks In order to determine the efficiency of biotinlabeled antibody produced, the direct ELISA was performed and the IBV antigen reacted specific against the respective antibody, producing an optical density pf 1.0 (DO), whilst the non-labeled antibody produced any OD [9][10][11][12] .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, basal lamina was infiltrated with mononuclear cells, presented submucosa oedema compatible with viral enteritis (results not shown). These findings have been described for PEMS, however they are common to other enteric pathogens [6][7][8] . Regarding to the intestines analyzed here, they were flaccid, thin-walled, and filled with loose contents, and the disease was acute, with symptoms appearing and lasting for about 3 weeks In order to determine the efficiency of biotinlabeled antibody produced, the direct ELISA was performed and the IBV antigen reacted specific against the respective antibody, producing an optical density pf 1.0 (DO), whilst the non-labeled antibody produced any OD [9][10][11][12] .…”
Section: Resultssupporting
confidence: 58%
“…In fact, Coronaviruses are in the family Coronaviridae, which are enveloped, positive-stranded RNA virus that infects a wide range of mammalian and avian species [6] . So far, Turkey Coronavirus (TCoV) and infectious bronchitis virus (IBV) belong to antigenic group III and share antigenic similarity [7] . This biological characteristic allows using antigen, as well as, antibodies raises against IBV, to develop and apply immunological tools for the TCoV diagnosis [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Some 25 years ago it was suggested that TCoV was closely related to BCoV of Group 2 (Dea et al ., 1990). We now know that this is not the case and that TCoV is unequivocally closely related to IBV, both in terms of gene and protein sequences (Breslin et al ., 1999a,b;Cavanagh et al ., 2001), and also antigenically (Guy et al ., 1997;Breslin et al, 2000;Loa et al ., 2000).…”
Section: Coronaviruses: the Three Groupsmentioning
confidence: 99%
“…They are pleomorphic positive-sense single-stranded RNA viruses measuring 60-220 nm in diameter. 3,11 The characteristic feature of the coronaviral morphology is the presence of long (12-24 nm), widely spaced petal-or pear-shaped surface projections, which impart to the virus the appearance of a solar corona. 14 Three structural proteins have been identified in the virus.…”
mentioning
confidence: 99%
“…5,11 The most widely used test for the serologic diagnosis of coronaviral enteritis is the indirect fluorescent antibody test. These procedures are labor intensive and time consuming.…”
mentioning
confidence: 99%